EXPLORING THE SYNERGY OF SYNCHRONOUS AND ASYNCHRONOUS LEARNING APPROACHES IN MEDICAL EDUCATION - Saxena, Ritcha; Carnewale, Kevin (IJRDO- Journal of Educational Research, 2023)
Advancements in technology have revolutionized medical education, offering new opportunities for exploration. The integration of innovative pedagogical strategies, accelerated by the COVID-19 pandemic, has extended beyond traditional classroom boundaries. Synchronous and asynchronous learning have emerged as dynamic approaches to enhance medical instruction. Synchronous learning fosters real-time engagement and interaction, promoting active participation and immediate feedback. Asynchronous learning encourages flexibility and self-paced exploration, enabling learners to access resources at their convenience and promoting autonomy and reflective learning. Both approaches have advantages and challenges. Challenges in synchronous learning include fixed schedules and technical disruptions, whereas asynchronous learning faces issues of limited interaction and self-motivation. By harmonizing these two modes through a blended approach, a seamless continuum of education unfolds. The integration of these methods creates a symphony of pedagogical innovation, catering to the diverse needs of medical learners. By skillfully orchestrating these modalities, educators can curate meaningful learning experiences aligned with the evolving landscape of medical education.